A Teaching Practice Design Based on a Computational Thinking Approach for Prospective Math Teachers Using Ed-tech Apps - Aminah, Neneng; Sukestiyarno; Wardono; Adi Nur Cahyono, (International Journal of Interactive Mobile Technologies (iJIM), 2022)
The pandemic situation forces us to use technology in learning. Likewise, prospective teachers who do field practice must prepare themselves to learn to use technology. So to overcome this, research was conducted to determine the validity, practicality, and responses of prospective teachers to the Computational Thinking (CT) based teaching practice model for mathematics teachers. This study uses Research and Development (R&D) with the ADDIE model, questionnaire validation, practicality questionnaire and teacher candidate response questionnaire used in the study. The results showed that the design of teaching practice based on the CT approach was very feasible to use, marked by the results of validation, practicality and positive responses from prospective teachers to the practice model used, as well as an increase in creativity of teaching practice. We recommend a CT-based teaching practice model using Ed-Tech on a hybrid learning system. This research is still limited to the mathematics department and for future researchers to carry out this practice in other majors in the university environment.